Needs of Learning Conditions for Student Learning Activities in Classroom - Yusuf, Faidah; Thalib, Syamsul Bachri; Gani, Hamsu Abdul (International Journal for Educational and Vocational Studies, 2020)
The aim of this study is to determine the classroom conditions for student learning activities. This was quantitative and qualitative research, conducted on 40 subjects, using the questionnaire as an instrument. The results identified five conditions, including (1) The learning strategy practiced, as lecturers tend to use various offline methods in the classroom, which need to be upgraded to online-based models. (2) The condition of course material utility, which was assessed to already be good, although improvement is also necessary, through the use of various models, including Facebook online live study. (3) The state of the facilities also needs to be improved in terms of air conditioners and internet signals with fast network access capacity, in order to ensure proper online-based learning. (4) Lecturer competency; The analysis results of this section have an impact on knowledge, in relation to online learning, therefore properly increasing Internet technology literacy. (5) Student characteristics, which are explained already, characterized by online learning with good knowledge of social media.